Pleiotropic Roles of P2X7 in the Central Nervous System - Kanellopoulos, Jean M.; Delarasse, Cécile (Frontiers in Cellular Neuroscience, 2019)
ATP is a signalling molecule that can act as a neurotransmitter in physiological conditions or as a danger signal when released in high amount by damaged/dying cells or activated glial cells. Thus, ATP is a danger-associated molecular pattern. ATP stimulates the purinergic receptor P2X7R leading to activation of different biochemical pathways, depending on the physiological or pathological environment. P2X7R is expressed by neural and immune cells, both cell types that are known to be involved in neurological diseases. The aim of this review is to discuss various functions of P2X7R in the immune and central nervous systems. We present evidence that P2X7R may have a detrimental or beneficial role in the nervous system, in the context of neurological pathologies: epilepsy, Alzheimer’s disease, multiple sclerosis, amyotrophic lateral sclerosis, age-related macular degeneration and cerebral artery occlusion.